Kekuatan Email Sebagai Alat Bukti dalam Proses Persidangan Perkara Perdata - Cokorda Agung Cahaya Darmadi; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
The rapid development of technology and telecommunications makes it easier for someone to send a letter via e-mail because the use of e-mail is considered cheap and fast. In addition, the data that we send via email will be stored, so that if at any time there is a problem related to the letter, it is easy to find physical evidence of the letter in the email. From this phenomenon, this research was conducted with the aim of examining how to prove the use of email based on the ITE Law and examine the strength of email in the trial process when it is associated with article 1866 of the Civil Code. This study uses a normative legal research type by applying the legislation approach and the case approach. The legal materials used are primary, secondary and tertiary obtained through literature study. After the data is collected, the data is processed by descriptive qualitative analysis. The results of the study show that e-mail verification as evidence in civil case trials can be used in trials regarding the legal aspects of e-mail application in enforcing the law. With the development of today's technology through communication media known as the internet, it has changed the way of thinking and acting which then has an impact on the law. The strength of e-mail evidence as a process of proof in court when it is associated with Article 164 HIR regarding valid evidence.